5 - La participation citoyenne en contexte local au Cameroun. Entre demande de légitimité, efficacité versatile et tensions politiciennes. - Calvin Minfegue (African Sociological Review, 2016)
This paper aims to analyze citizen engagement in Cameroonian context. Through an overview of the vulgarization of a discourse on participation, it analyses the main models accompanying them in some local scale studies, which operationalizes the concept. In this way, citizen engagement at local level seems to be located between three points of tension: need of legitimacy, irregular efficacy and strong logics of political appropriation.